The Effect of Cluster Position Determined by Vineyard Row Orientation on Grape Flavonoids and Aroma Profiles of Vitis vinifera L. cv. Cabernet Sauvignon and Italian Riesling in the North Foot of Tianshan Mountains - Lu, Hao-Cheng; Gao, Xiao-Tong; Duan, Chang-Qing; Li, Shu-De; Chen, Wu; Wang, Jun (South African Journal of Enology and Viticulture, 2021)
Vineyard row orientation plays a critical role in determining cluster microclimate. This study aimed to figure out how cluster positions determined by vineyard row orientation affect grape flavonoids and aroma profiles of Cabernet Sauvignon and Italian Riesling grapes. Three cluster positions (two canopy sides and the inner canopy) of NS and EW oriented row Cabernet Sauvignon and NS oriented row Italian Riesling were selected for the experiment. Microclimate data was monitored around clusters from both canopy sides of different row orientations. The south canopy side had higher daytime temperatures and PAR than the north canopy side in EW row orientation. Flavonoids of grape skins and seeds were separated and determined by LC-MS, and aroma compounds of grape must were determined by GC-MS. Results showed that flavanols were affected by orientations, and EW orientation had higher berries skin flavanol concentration than NS orientation. EW-IN berries had fewer glucuronide form flavonols and 3’-hydroxylated flavonols than the other two positions in EW orientation. Inner canopy berries had lower flavonol concentration than other positions in EW orientation of CS and NS orientation of IR. To aromas, C6/C9 were the main compounds significantly affected by row orientations. EW orientation berries had higher C6 alcohols concentration such as (E)-3-Hexen-1-ol, (E)-2-Hexen-1-ol and (Z)-3-Hexen-1-ol than NS orientation, while NS orientation berries had higher C6 aldehyde concentrations such as Hexanal and (E)-2-hexenal than EW orientation. EW-IN berries had more abundant C6/C9 compounds than the other two positions. The study provided preliminary scientific evidence for vineyard viticulture practice and harvest strategy.